Did the COVID-19 Recession Increase the Demand for Digital Occupations in the United States? : Evidence from Employment and Vacancies Data - Soh, Jiaming (IMF Working Papers; Working Paper ;, 2022)
This paper investigates whether the COVID-19 recession led to an increase in demand for digital occupations in the United States. Using O*NET to capture the digital content of occupations, we find that regions that were hit harder by the COVID-19 recession experienced a larger increase in the share of digital occupations in both employment and newly-posted vacancies. This result is driven, however, by the smaller decline in demand for digital workers relative to non-digital ones, and not by an absolute increase in the demand for digital workers. While our evidence supports the view that digital workers, particularly those in urban areas and cognitive occupations, were more insulated during this recession, there is little indication of a persistent shift in the demand for digital occupations.